Quality of Life of Hemodialysis Patients in the Sidikalang Regional General Hospital - Silaban, Jojor; Hasianna, Vanesha; Silaban, Verawaty Fitrinelda (Universitas Prima Indonesia, 2024)
Patients undergoing hemodialysis have become a health problem that is becoming a trend in society, where the prevalence is increasingly high. Hemodialysis is very important as a treatment therapy but not as a therapy to cure. The impact of hemodialysis therapy is that patients are vulnerable to emotional problems such as stress related to restrictions on diet and fluid intake, physical limitations, disease conditions, drug side effects, and dependence on dialysis. This research aims to describe the quality of life of hemodialysis patients. The type of research used was a descriptive survey, carried out at Sidikalang District Hospital, Dairi Regency. The population of this study was 42 hemodialysis patients. The sampling technique includes total sampling and an accidental sampling approach. Data analysis using univariate analysis to describe the quality of life of hemodialysis patients. The results showed that the majority of hemodialysis patients' quality of life was moderate, with 34 people (80.96%); each quality of life aspect domain shows that the majority in the physical health domain is poor with 25 people (59.52%), the majority in the psychological domain is poor with 31 people (73.80%), the majority in the social relations domain is good with 20 people (47.61%), and the environmental domain has a bad majority of 20 people (47.61%). Health workers in the hemodialysis unit are expected to play a role in providing health education about maintaining the physical, and psychological health, social relationships, and environment of hemodialysis patients through leaflets or watching educational videos during the process.